2022
DOI: 10.3390/molecules27144488
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anthelmintic and Anti-Inflammatory Activity of 1,2,4-Triazole Derivatives

Abstract: Parasitic diseases, caused by intestinal helminths, remain a very serious problem in both human and veterinary medicine. While searching for new nematicides we examined a series of 1,2,4-triazole derivatives 9–22, obtained during reactions of N3-substituted amidrazones with itaconic anhydride. Two groups of compounds, 9–16 and 17–22, differed in the position of the double bond on the methacrylic acid moiety. The toxicity of derivatives 9–22 and the anti-inflammatory activity of 12 and 19–22 were studied on per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 51 publications
(111 reference statements)
0
19
0
Order By: Relevance
“…The 1,2,4-triazole derivative 51 , obtained from amidrazone, showed strong anthelmintic activity (2.475 µg/µL) against Rhabditis nematodes. Due to its stronger activity than albendazole and low toxicity to PBMC, compound 51 could be a candidate for the development of new anthelmintic drugs [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1,2,4-triazole derivative 51 , obtained from amidrazone, showed strong anthelmintic activity (2.475 µg/µL) against Rhabditis nematodes. Due to its stronger activity than albendazole and low toxicity to PBMC, compound 51 could be a candidate for the development of new anthelmintic drugs [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some 1,2,4-triazole derivatives obtained by the cyclisation of amidrazones, similar to 56 – 57 , showed a strong significant anti-inflammatory activity comparable to ibuprofen’s inhibition of PHA-stimulated PBMC proliferation and TNF-α production [ 46 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the PBMC stimulation assay is widely used for assessing anti-inflammatory activity in IBD research [ 258 , 259 , 260 ]. Paprocka et al investigated the anti-inflammatory activity of five natural SMs using LPS- LPS-stimulated PBMC, which showed that all derivatives significantly inhibited the production of pro-inflammatory cytokines, TNF and IFN-γ [ 261 ]. In another study, IPX-18 suppressed the production of IFN-γ, TNF, IL-8 and IL-2, with an IC 50 value of 96.29, 103.7, 122.9 and 105.2 nM by PBMC induced with 50 ng/mL of phorbol-12-myristate-13-acetate (PMA) [ 262 ].…”
Section: Screening Isolated Compounds For Anti-inflammatory Propertiesmentioning
confidence: 99%
“…Further, the Anthelmintic and Antiproliferative activity of compounds studied in the Rhabditis sp and PBMC cultures stimulated by phytohemagglutinin. [148] Osmaniye's group mentioned the design and synthesis of 16 new thiadiazoles as non-selective COX inhibitors. Compound 51 shows anti-inflammatory activity similar to the standard celecoxib.…”
Section: Miscellaneous Heterocycles As Anti-inflammatory Agentsmentioning
confidence: 99%
“…Also, compounds 49 and 50 a – d significantly reduced the production of TNF‐α and the level of INF‐γ determined by ELISA in lipopolysaccharide‐stimulated PBMC cultures. Further, the Anthelmintic and Antiproliferative activity of compounds studied in the Rhabditis sp and PBMC cultures stimulated by phytohemagglutinin [148] …”
Section: Small Molecules As Potent Anti‐inflammatory Agentsmentioning
confidence: 99%